1994
DOI: 10.1161/01.cir.90.2.694
|View full text |Cite
|
Sign up to set email alerts
|

Increased secretion of tumor necrosis factor-alpha and interferon-gamma by mononuclear leukocytes in patients with ischemic heart disease. Relevance in superoxide anion generation.

Abstract: Similar increases in cytokine secretion by mononuclear leukocytes in stable or unstable angina pectoris indicate that the increased cytokine release is not a nonspecific inflammatory response in acute myocardial ischemia. Increased cytokine secretion in ischemic heart disease may play a role in superoxide radical generation, endothelial injury, deposition and activation of cellular elements on the vessel wall, and possibly in the progression of atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
0
7

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(73 citation statements)
references
References 35 publications
5
61
0
7
Order By: Relevance
“…23 This could contribute to the observed increase of XDH/XO in patients with CAD because increased secretion of interferon-␥ by activated T-lymphocytes has been demonstrated in human atherosclerotic arteries. 24 Furthermore, experimental studies support the concept that activation of the renin-angiotensin system may contribute to increased vascular XO activity, because inhibition of XO could markedly improve endothelium-dependent vasodilation in reninangiotensinogen-overexpressing rats. 25 During the past decade, several O 2 ·Ϫ -forming enzyme systems using NAD(P)H as a cofactor have been identified in vascular cells that may contribute to NADPH-dependent O 2 ·Ϫ production, such as the vascular isoforms of the leukocyte NAD(P)H oxidase, 26 XO 27 , cytochrome-P450 28 and the uncoupled NO synthase.…”
Section: Discussionmentioning
confidence: 93%
“…23 This could contribute to the observed increase of XDH/XO in patients with CAD because increased secretion of interferon-␥ by activated T-lymphocytes has been demonstrated in human atherosclerotic arteries. 24 Furthermore, experimental studies support the concept that activation of the renin-angiotensin system may contribute to increased vascular XO activity, because inhibition of XO could markedly improve endothelium-dependent vasodilation in reninangiotensinogen-overexpressing rats. 25 During the past decade, several O 2 ·Ϫ -forming enzyme systems using NAD(P)H as a cofactor have been identified in vascular cells that may contribute to NADPH-dependent O 2 ·Ϫ production, such as the vascular isoforms of the leukocyte NAD(P)H oxidase, 26 XO 27 , cytochrome-P450 28 and the uncoupled NO synthase.…”
Section: Discussionmentioning
confidence: 93%
“…It was reported that antioxidants played a role in HDL cholesterol. 14 Oxidants influence the balance of the coagulation system toward platelet aggregation and thrombus formation. 15 Low HDL cholesterol is a coronary risk factor and may also be a prognostic factor of failed coronary reperfusion therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory status plays key roles in undermining atherosclerotic plaque stability (7,(17)(18)(19), which leads to lifethreatening AcS. Metabolic disorders are closely associated with atherosclerosis inflammation (20).…”
Section: Discussionmentioning
confidence: 99%